(untitled) (Journal of Sciences & Technology, 2018)
The paper presents the influence of the thermal inertia on the temperature of a heated concrete slab. This is a solar sensor provides a solar heating system floor, which the energy input. The concept of thermal inertia is not easy to grasp. It is defined as the speed that helps a system ((building in our case) reacts to the change in operating conditions. The response of the building facing to the stresses is largely depending on the thermal properties of constituent materials. This feature is related to good performance, good use, and comfort of the thermal machine which is called ‘‘habitat’’. The objective of this work aims to study the influence of the inertia on the surface temperature of the floor, to design the future of homes with high inertia and very low energy consumption with satisfactory comfort conditions.